Study on solid electrolyte interphase excessive growth caused by Mn (II) deposition on silicon anode. (20th August 2018) - Chen, Haihui; Ma, Tianyi; Zeng, Yingying; Liu, Limin; Qiu, Xinping
Abstract: Silicon has been considered as one of the next generation high capacity anode materials. However, dissolution of cathode material in electrolyte, which is a general problem for lithium-ion batteries, hinders the industrial development of silicon anode. This paper designs electrochemical environment of Mn (II) dissolution to study the capacity fading of silicon anode. Electrochemical analysis and differential scanning calorimetry analysis reveals that Mn (II) will decrease the stability of solid electrolyte interphase, leading to acceleration of solid electrolyte interphase excessive growth and decreasing Columbic efficiency of anode.